Digital World of Children and Youth - Aleksander Piecuch (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
The article discusses the issue of the use of modern technologies by children and youth. The age at which children begin their active participation in the virtual space has already fallen to seven years. The amount of time children and young people spend on online activity is also gradually increasing. The type of activity to which the virtual space is used by young people, and the question of whether these trends can, or perhaps should be used in school education, is an interesting aspect.